THE IMPLEMENTATION OF SCHOOL BASED-CURRICULUM IN TEACHING ENGLISH TO THE FIFTH GRADES OF SDN 01 BANYUANYAR SURAKARTA IN 2009/2010 ACADEMIC YEAR - PUTRIANTI, ERIKA (2010)
This research aims at analyzing the implementation of School based-Curriculum in teaching English to the fifth grade of SDN 01 Banyuanyar Surakarta in 2009/2010 academic year and knowing the problems faced by the teacher in implementing School -based Curriculum to in SDN 01 Banyuanyar Surakarta in 2009/2010 academic year. This research is a qualitative research. The data are taken from document, interview, and observation analysis. The object of the study is teaching English for the fifth grade students of SDN 01 Banyuanyar SURAKARTA. The result of study shows that the implementation of School based-Curriculum in teaching English to the fifth grade of SDN 01 Banyuanyar Surakarta in 2009/2010 academic year is not clear. Firstly teacher gives a clear explanation about the material to create a descriptive text based on the picture. The teacher uses a simple material for the student in elementary school level. The teacher teaches the material based on the curriculum so the students are able to follow the lessons. The implementation achieved by the student proved that they are more interested in English; the material makes the student able to follow the lesson without any problem because in teaching English at SDN 01 Banyuanyar the teacher applies two techniques of teaching English such as acting from a script and discussion. The acting from the script action is the teacher uses picture which is the picture related to descriptive text. The students must create their own word (descriptive text) based on the picture given then on the discussion the students and the teacher do a discussion to study the student's ability after the work. The problem faced by the teacher in implementing school level based curriculum in SD Banyuanyar 01 has two problems by the English teacher of elementary school. The problems that the teacher faced are as follow information about KTSP is low process in transferring the information about school based curriculum, lack of facilities/ teaching Medias which is availability of teaching facility is far from complete.